Pengaruh Struktur Kepemilikan dan Leverage Terhadap Return Saham - Susilowati, Eko Meiningsih (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
The objective to be achieved in this study was to provide empirical evidence that ownership structure and leverage affected positively the  stock  return in manufacturing companies in Indonesian Effect Stock (ISE). The population of research  was go public companies  enlisted  in  ISE.  The  sample  was  taken  using  purposive  sampling  technique aiming  to  obtain  sample  corresponding  to  the  research  objective,  consisting  of  45 sample  companies.  The  result  of  research  showed  that  ownership  structure  variable affected  positively  the  stock  return.  Meanwhile,  leverage  variable  affected  negatively. Ownership  structure  and  leverage  simultaneously  did  not  affect  stock  return  variable. The  result  of  determination  test  showed  that  ownership  structure  and  leverage  could explained a little of stock return variable only